2022
DOI: 10.1029/2021jc018228
|View full text |Cite
|
Sign up to set email alerts
|

Pathways, Form Drag, and Turbulence in Simulations of an Ocean Flowing Through an Ice Mélange

Abstract: Introduction The Roles of a Mélange in a Glacial FjordThe advance and retreat of Greenland's marine terminating glaciers is partly controlled by the exchange of heat between ice and ocean. This, in turn, depends on the rate at which waters near the glacier are renewed. One influence on this renewal is the mélange, a mixture of sea ice and icebergs that typically extends several kilometers in front of the glacier. For example, in Sermilik Fjord, a large fjord on Greenland's southeast coast, the mélange is typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…These results are consistent with prior studies at Sermeq Kujalleq, which found strong glacier‐mélange linkages and weak to null mélange‐ocean current linkages (Amundson et al., 2010; Cassotto et al., 2021). Additionally, modeled outputs suggest that surface currents in a mélange are greatly reduced, and instead of flowing at the surface, the down‐fjord flow is located below the drafts of the deepest icebergs (Hughes, 2022). Therefore, due to the tightly packed nature of the mélange and the forced location of the currents, tracking icebergs in the mélange region is not representative of fjord circulation and we exclude the mélange region in analysis of surface circulation.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with prior studies at Sermeq Kujalleq, which found strong glacier‐mélange linkages and weak to null mélange‐ocean current linkages (Amundson et al., 2010; Cassotto et al., 2021). Additionally, modeled outputs suggest that surface currents in a mélange are greatly reduced, and instead of flowing at the surface, the down‐fjord flow is located below the drafts of the deepest icebergs (Hughes, 2022). Therefore, due to the tightly packed nature of the mélange and the forced location of the currents, tracking icebergs in the mélange region is not representative of fjord circulation and we exclude the mélange region in analysis of surface circulation.…”
Section: Discussionmentioning
confidence: 99%
“…found strong glacier-mélange linkages and weak to null mélange-ocean current linkages (Amundson et al, 2010;Cassotto et al, 2021). Additionally, modeled outputs suggest that surface currents in a mélange are greatly reduced, and instead of flowing at the surface, the down-fjord flow is located below the drafts of the deepest icebergs (Hughes, 2022). Therefore, due to the tightly packed nature of the mélange and the forced location of the currents, tracking icebergs in the mélange region is not representative of fjord circulation and we exclude the mélange region in analysis of surface circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Very high‐resolution (<10 m) models have brought insight into the dynamics of subglacial discharge plumes (e.g., Carroll et al., 2015; Ezhova et al., 2017; Kimura et al., 2014; Sciascia et al., 2013; Xu et al., 2012) and led to plume representation into larger fjord models (T. Cowton et al., 2015; Jenkins, 2011; Rignot et al., 2016). Fjord‐scale models have allowed for an assessment of the impact of along‐fjord winds, along‐shelf winds and shelf forcing on fjord dynamics (Fraser & Inall, 2018; Jackson et al., 2018; Sundfjord et al., 2017), of iceberg melt on water mass transformation (Davison et al., 2020; Kajanto et al., 2023), of sea ice retreat on fjord circulation (Shroyer et al., 2017), and of fjord geometry, including ice mélange, on fjord renewal (Gladish, Holland, Rosing‐Asvid, et al., 2014; Carroll et al., 2017; Zhao et al., 2021; K. G. Hughes, 2022). While these models have significantly improved our understanding of glacial fjord processes, they are usually run on idealized bathymetry or with idealized forcing limiting any comparison with observations.…”
Section: Introductionmentioning
confidence: 99%